PREDIKSI JUMLAH SEL LIMFOSIT T CD4+ MENGGUNAKAN NILAI TLC (TOTAL LYMPHOCYTE COUNT) PADA PENDERITA HIV/AIDS - Rostina Rostina; Suci Aprianti; Mansyur Arif (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2008)
AIDS is a severe disease caused by Human Immunodeficiency Virus (HIV) that affects patient’s immune system, especially CD4+ Tcells (CD4). Hence, CD4 count is used as parameter to starting ARV treatment or monitoring the progress of the disease. However, themeasurement of CD4 is expensive and available in big hospitals. In small or remote hospitals there are no means to measure the CD4.Some studies suggest that in an area where CD4 count is unavailable, the total lymphocyte count (TLC) of HIV/AIDS patients can roughlybe used to predict CD4 values. This study is aimed to see whether the TLC values can be used to roughly predict the CD4 count of HIV/AIDS patients and to formulate the correlation form between them. A cross sectional study design was applied to 79 blood samples ofHIV/AIDS patients from Clinical Pathology Laboratory of Wahidin Sudirohusodo Hospital from January to September 2007. The bloodsamples were tested for TLC as well as CD4 values. The correlation of TLC and CD4 values was tested with Pearson Correlation Test andthe correlation formula was derived from curve estimation of Regression Analysis. Sensitivity, specificity, PPV and NPV of various cutpoint of TLC (1000, 1200, 1500, 2000) to predict CD4 < 200/ul were determined using cross tabulation Fisher Exact Test. A positivecorrelation was found between TLC and CD4 count (R = 0.528, p < 0.001) with the regression formula is CD4 = 0.09TLC – 1.42.The WHO standard cut point TLC1200/ul give best result for sensitivity, specificity, PPV and NPV: 80.6%, 91.7%, 98.2% and 45.8%,respectively. The cut point of TLC1200 can be used to roughly predict CD4 < 200/ul of HIV/AIDS patients, so, can be use as a mark forstarting ARV therapy in the place were measurement of CD4 is unavailable